THU0657 A tele-health follow-up strategy for tight control of disease activity in rheumatoid arthritis: results of the non-inferiority randomised controlled trail (the tera study). (15th June 2017) - Thurah, A; Steengaard-Pedersen, K; Axelsen, M; Fredberg, U; Schougaard, LMV; Hjøllund, NHI; Pfeiffer-Jensen, M; Laurberg, TB; Lomborg, K; Maribo, T
Abstract : Background: Despite the increased prevalence of rheumatoid arthritis (RA) in recent years, no studies have yet investigated the effect of monitoring disease activity through a standardized tele-health strategy in patients with RA (1). Objectives: To test the effect of patient-reported outcome (PRO) based tele-health follow-up for tight control of disease activity in patients with RA, and the differences between tele-health follow-up performed by rheumatologists or rheumatology nurses. Methods: A total of 294 patients were randomized (1:1:1) to either PRO-based tele-health follow-up carried out by a nurse (PRO-TN) or a rheumatologist (PRO-TR), or conventional out-patient follow-up by physicians. The Flare-RA (2) was used as decision aid for assessing disease activity. The primary outcome was change in DAS28 after week 52. Secondary outcomes were: physical function, quality of life and self-efficacy. The non-inferiority margin was a DAS28 change of 0.6. Mean differences were estimated following per-protocol, intention to treat (ITT) and imputation (IMP). Results: Overall patients had low disease activity at baseline and end follow-up. Demographics and baseline characteristics were similar between groups. Non-inferiority was established for DAS28. In the ITT analysis mean difference in DAS28 between PRO-TR vs. control were -0.10 (90% CI -0.30; 0.13) and -0.19 (-0.41; 0.02) between PRO-TN vs. control. When including one yearly visit to the outpatient clinic, patients in PRO-TN had a total of 1.72 (SD 1.03) visit/year, PRO-TR 1.75 (SD 1.03) vist/year and control 4.15 (SD 1.0) visits/year. This included extra visits due to inflammatory flare. Overall more than 80% of the patients in all three groups answered that they were "very satisfied" with the consultation form they received and no differences were found between the three groups. Conclusions: Among RA patients with low disease activity or remission a PRO-based tele-health follow-up for tight control of disease activity in RA can achieve similar disease control as conventional outpatient follow-up. The degree of disease control did not differ between patients seen by rheumatologists or rheumatology nurses. References: References. Ward IM, Schmidt TW, Lappan C, Battafarano DF. How critical is tele-medicine to the rheumatology workforce? Arthritis Care Res (Hoboken). 2016 Feb 11. Berthelot JM, De Bandt M, Morel J, Benatig F, Constantin A, Gaudin P, et al. A tool to identify recent or present rheumatoid arthritis flare from both patient and physician perspectives: The 'FLARE' instrument. Ann Rheum Dis. 2012 Jul;71(7):1110–6. ClinicalTrails.gov identifier: NCT02155894 . Disclosure of Interest: None declared